Mohammed Arkoun’s Thought on Sharia Deconstruction: A Historical and Anthropological Approach - Makmun Syar'i (Mazahib, 2022)
This article explores Mohammad Arkoun’s thoughts on understanding Islamic Sharia in the modern world. Arkoun’s thought differs from previous Islamic thinkers in analyzing Islamic texts. Arkoun exceeded the limit of traditional Islamic studies by utilizing several elements from Modern Western philosophy, social sciences, and humanities. Arkoun took this effort to realize his ambition, which was the combination of valuable thoughts from Islamic notions and modern philosophy. In the philosophy of Islamic law, the combination in line with the particular theorem stated: “al-muhāfaẓah `alā al-qadīm al-ṣālih wa al-akhdzu `alā al-jadīd al-aṣlah” (literary means keeping good old traditions and adopting a new better ones). Islamic sharia should be related to historical context. According to Arkoun, the traditional and textual paradigm in understanding Islamic sharia leads people to misunderstand Quranic interpretation. People sanctify Islamic thoughts instead of understanding the substantial meaning behind the Quranic texts. Arkoun called this phenomenon “taqdīs al-Afkār ad dīniyyah” (sanctifying religious thoughts). This study finds that Arkoun’s thoughts are close to an anthropological and historical approach. The Quranic interpretation has to look at both universal and particular texts of the Quran by deconstructing the logic and discourse that underlay the emergence of these texts. Keywords: Muhammad Arkoun, Quranic interpretation, sharia deconstruction, historical and anthropological approach.